The mental representation of the smile before and after orthodontic treatment - Dias, Maria do Rosário (2021)
Submitted by Paula Saraiva (psaraiva@egasmoniz.edu.pt) on 2021-06-18T10:47:12Z No. of bitstreams: 1 Capítulo_MRDias_2021_01_Final.pdf: 373453 bytes, checksum: f13fa8bae3c5f2a62a1d8d8f8a855a29 (MD5)